2022
DOI: 10.2196/35325
|View full text |Cite
|
Sign up to set email alerts
|

Audio Recording Patient-Nurse Verbal Communications in Home Health Care Settings: Pilot Feasibility and Usability Study

Abstract: Background Patients’ spontaneous speech can act as a biomarker for identifying pathological entities, such as mental illness. Despite this potential, audio recording patients’ spontaneous speech is not part of clinical workflows, and health care organizations often do not have dedicated policies regarding the audio recording of clinical encounters. No previous studies have investigated the best practical approach for integrating audio recording of patient-clinician encounters into clinical workflow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…No secure or privacy-by-design systems were identified in any of the studies found involving data collection [ 53 , 54 , 55 ]. In cases where security is addressed, it is usually not directed at the recording devices or the security of the data stored in it, but at security of web servers where these data are stored, down in the data management pipeline [ 56 ], with some systems adopting questionable privacy practices such as passing patient voice data onto web-based services for transcription and often for storage [ 57 ]. Nor are security and privacy requirements usually adhered to in ad hoc recordings often made in clinical practice, either by the clinician or (less commonly) by the patient [ 58 ], with unclear legal implications [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…No secure or privacy-by-design systems were identified in any of the studies found involving data collection [ 53 , 54 , 55 ]. In cases where security is addressed, it is usually not directed at the recording devices or the security of the data stored in it, but at security of web servers where these data are stored, down in the data management pipeline [ 56 ], with some systems adopting questionable privacy practices such as passing patient voice data onto web-based services for transcription and often for storage [ 57 ]. Nor are security and privacy requirements usually adhered to in ad hoc recordings often made in clinical practice, either by the clinician or (less commonly) by the patient [ 58 ], with unclear legal implications [ 59 ].…”
Section: Discussionmentioning
confidence: 99%